From objects to diagrams for ranges of functors - Gillibert, Pierre; Wehrung, F. 1961- (Friedrich).; SpringerLink (Online service). (Berlin Heidelberg New York Springer-Verlag, 2011)
This work introduces tools from the field of category theory that make it possible to tackle a number of representation problems that have remained unsolvable to date (e.g. the determination of the range of a given functor). The basic idea is: if a functor lifts many objects, then it also lifts many (poset-indexed) diagrams.
1 Background -- 2 Boolean Algebras Scaled with Respect to a Poset -- 3 The Condensate Lifting Lemma (CLL) -- 4 Larders from First-order Structures -- 5 Congruence-Preserving Extensions -- 6 Larders from von Neumann Regular Rings -- 7 Discussion.
Electronic reproduction.
Keywords: Functor theory; Algebra, Boolean; Algebraic logic; Electronic books